Given that y = (1 + 3x^2)^(1/3) , use the chain rule to find dy/dx in terms of x.

Take u = 1+3x2 , this gives that y = u1/3 . By the chain rule we have that dy/dx = dy/du * du/dx. By differentiating y = u1/3 with respect to u gives dy/du = (1/3)u-2/3. By differentiating u = 1 + 3x2 with respect to x gives du/dx = 6x. Using the formula highlighted gives the answer dy/dx = 2x(1+3x2)-2/3 which we have obtained by substituting u back in.

Answered by Jasmine S. Maths tutor

3833 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find, in radians, the general solution of the equation cos(3x) = 0.5giving your answer in terms of pi


Show that (sec(x))^2 /(sec(x)+1)(sec(x)-1) can be written as (cosec(x))^2.


The velocity of a car at time, ts^-1, during the first 20 s of its journey, is given by v = kt + 0.03t^2, where k is a constant. When t = 20 the acceleration of the car is 1.3ms^-2, what is the value of k?


What is a stable solution and what is dominance?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences